Potential Hollowfiber Polyurethane-Collagen of Chitosan Coatings As a Nerve Graft for the Therapy of Peripheral Nerve Injuries in Limb Paralysis - Maulida, Hendita (Journal of Stem Cell Research and Tissue Engineering, 2018)
Peripheral nerve injury with a gap of 5–30 mm can cause permanent paralysis because it causes an axon to break up. The distance between axons of more than 1-2 cm requires a graft in the form of a nerve connector to fix it. Synthesis of chitosan coated polyurethane-collagen hollowfiber has been carried out as an accelerator for healing peripheral nerve injury. The results of Fourier Transform Infra Red (FTIR) analysis showed a cross link between chitosan and glutaraldehyde seen in the shift of wave numbers from 1080-1100 cm-1 to 1002 cm-1. The degradation test results showed that the sample experienced a decrease in mass after being immersed in Simulated Body Fluid (SBF) for 7 days. Polyurethane can be degraded in the body after 30 days. This is in accordance with the mechanism of the nerve which regenerates 1 mm per day or 1 inch per month. Scanning Electron Microscope (SEM) analysis showed that the diameter of the hollowfiber was 2.021-2.032 mm which corresponds to the peripheral nerve diameter of 1.5-3 mm and the pore size of the wall is 31.33-39.65 Î¼m. The results of this study are expected to provide the theoretical basis for the use of chitosan polyurethane-collagen coating composites as nerve grafts for the treatment of peripheral nerve injuries that have biocompatible properties, can regenerate and are easily degraded and provide alternative solutions for nerve graft needs that are more economical and easier to manufacture so widely produced in Indonesia.